Chemical proximate composition, antinutritional factors content, and antioxidant capacity of anatomical seed fractions of Moringa oleifera - Cuevas-Rodríguez, Edith Oliva; León-López, Liliana; Escobar-Zúñiga, Yudith; Milán-Carrillo, Jorge; Domínguez-Arispuro, Dulce María; Gutiérrez-Dorado, Roberto (Acta Universitaria, 2020)
For rational use of moringa seeds and its anatomical fractions (kernel, shells, and wings), the objective of the present investigation was to analyze their chemical composition, antinutritional factors content, and antioxidant capacity. The seed kernel fraction represents 71.78% of the whole seed weight and possesses high contents of protein (32.19%) and lipids (38.72%), whereas seed shells and wings fractions are mainly composed of dietary fiber and carbohydrates. Phytate was the most abundant antinutritional factor detected in all fractions (604.0 mg PAE/100 g-1674.9 mg PAE/100 g), followed by total phenolics (218.5 mg GAE/100 g-386.9 mg GAE/100 g) and saponins (130.4 mg DE/100 g-197.4 mg DE/100 g). Moringa seeds fractions showed a high antioxidant capacity. The kernel fraction exerts the highest activity (15 251.90 Î¼mol TE/100g), followed by shells (8 499.50 Î¼mol TE/100g) and wings (5 878.90 Î¼mol TE/100g). Moringa seed kernel fraction seems to be a promising source of protein. All anatomical seed fractions of moringa are a reservoir of dietary fiber and antioxidants.